Dylemat audiodeskryptora w procesie przekładu audiowizualnego - Wątrobiński, Damian (Investigationes Linguisticae, 2019)
The aim of this article is to point out the dilemma concerning the transmission of emotions which faces the audio descriptor when creating audio description for painting reproductions. It will indicate the importance of visual forms, dependencies between the translator, translation and emotions, as well as different approaches to the creation of audio description, with particular emphasis on the transfer of emotions. The theoretical considerations will be supplemented by a qualitative analysis of two emotionally colored audio descriptions.